Perencanaan Strategi Bersaing Madrasah Dalam Meningkatkan Jumlah Peserta Didik Di Madrasah Ibtidaiyah Kabupaten Bone - Muh. Bachtiar Aziz; Widia Sari (Institusi Agama Islam Negeri (IAIN) Bone, 2024)
The quantity of students in an educational institution is one of the success factors of an educational institution, in increasing the quantity of students it is very closely related to the competitive strategy planning of educational institutions, in order to increase the quantity of students it is necessary to have careful planning and be able to create a competitive strategy between institutions other education, therefore educational institutions must have the best quality in order to create an increase in the quantity of students, by using qualitative methods that are descriptive and with fact and data analysis techniques are expected to be able to analyze more deeply about madrasah competitive strategy planning in increasing the number of students. The results of the study show that competitive strategic planning plays an important role in increasing the quantity of students, as evidenced by the formation of several programs that are used as competitive strategies which are expected to be able to attract public interest, especially prospective students. Furthermore, the implementation of each program that has been formed is the main thing that will determine the success of the previously prepared plans, but also requires controlled and consistent control, so that there are no obstacles that cause ineffectiveness and inefficiency of the programs that have been prepared before.